Electric utility vulnerability to wildfires and post-fire debris flows in California - Eleanor M Hennessy; Mikhail V Chester (Environmental Research: Infrastructure and Sustainability)
Wildfires and post-fire debris flows (PFDFs) threaten California infrastructure and are evolving with climate change. There is significant focus on the threat of utility-caused wildfires because electric power equipment has triggered wildfires leading to major damage. California’s ambitious climate targets rely on electrification of transport and industry. As the state modernizes its electricity system to support increased demand, it must consider future climate hazards. To date, there is no rigorous characterization of the intersection of future fire threat, PFDFs, and electrical infrastructure. We estimate wildfire and PFDF threat to transmission lines, substations, and power generators in California and assess vulnerability of electric utilities by intersecting electrical infrastructure and current and future wildfire and PFDF threat, using two global climate models and two representative concentration pathways. We find clean, dispatchable power generators (e.g. hydroelectric and nuclear) and small, publicly-owned utilities are most vulnerable. Increasing threats will require additional resources and consideration of future threat distribution.